1995
DOI: 10.1002/hep.1840220602
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon-alfa therapy in children with chronic hepatitis C

Abstract: The efficacy of recombinant interferon-alfa therapy in children with chronic hepatitis C has been evaluated in a randomized, controlled pilot study including 27 patients, aged 2 to 14 years, without underlying systemic diseases. On entry, all patients had abnormal alanine transaminase (ALT) levels, 22 were hepatitis C virus (HCV) RNA positive, 19 had mild chronic active hepatitis, and 8 had chronic persistent hepatitis on liver biopsy. Fourteen children received 5 MU/m2 of recombinant interferon-alfa2b thrice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 23 publications
3
44
0
1
Order By: Relevance
“…These results were borderline statistically significant (p = 0.056), likely due to the small numbers of patients. Bortolotti et al reported that SVR was achieved in 9 of 13 (69%) treated patients and 0 of 13 controls (p<0.001) [17]. Almost all treated patients had flu-like symptoms, and doses of interferon were decreased in 7 of 25 children (28%) due to neutropenia.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…These results were borderline statistically significant (p = 0.056), likely due to the small numbers of patients. Bortolotti et al reported that SVR was achieved in 9 of 13 (69%) treated patients and 0 of 13 controls (p<0.001) [17]. Almost all treated patients had flu-like symptoms, and doses of interferon were decreased in 7 of 25 children (28%) due to neutropenia.…”
Section: Resultsmentioning
confidence: 98%
“…Three included only pediatric populations [17], [18], [19] while one had a mixed pediatric-adult population [20]. All four RCTs were deemed to have an unclear risk of bias based on the Cochrane Risk of Bias tool.…”
Section: Resultsmentioning
confidence: 99%
“…However, data on the natural history of chronic hepatitis C in children are limited [1,2,6,9]. We monitored the clinical courses of children with chronic hepatitis C to clarify the natural history of the disease and to compare the characteristics of the children with and without spontaneous remission.…”
Section: Introductionmentioning
confidence: 99%
“…IFN has been reported to induce responses in children with chronic hepatitis C comparable to or greater than those in adults [1,2,4]. All previous therapeutic trials treated small numbers of children and did not evaluate factors influencing the response.…”
mentioning
confidence: 97%